2016
DOI: 10.1097/md.0000000000003665
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL12A Expression Quantitative Trait Loci (eQTL) With Primary Biliary Cirrhosis in a Chinese Han Population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…More recently, specific PBC populations have been found to have diminished IL-12A production [24], and a clinical trial using the IL-12 inhibitor ustekinumab showed no efficacy [25], suggesting that patients may lack IL-12 activity. Epidemiological studies also indicate that PBC patients may lack immune function with both an increased prevalence of infectious diseases, such as tonsillitis and urinary tract infection, and an increased prevalence of cancers, such as lymphoma, thyroid, kidney, and breast cancer [7,26,27].…”
Section: Pbc: Genes Vs Environmentmentioning
confidence: 99%
“…More recently, specific PBC populations have been found to have diminished IL-12A production [24], and a clinical trial using the IL-12 inhibitor ustekinumab showed no efficacy [25], suggesting that patients may lack IL-12 activity. Epidemiological studies also indicate that PBC patients may lack immune function with both an increased prevalence of infectious diseases, such as tonsillitis and urinary tract infection, and an increased prevalence of cancers, such as lymphoma, thyroid, kidney, and breast cancer [7,26,27].…”
Section: Pbc: Genes Vs Environmentmentioning
confidence: 99%
“…The statistical analysis was primarily carried out as previously reported. [ 18 19 ] A PLINK tool set (Broad Institute, MA, USA) was used to conduct the association analysis. [ 20 ] The Chi-square test was applied to compare allele frequencies between case and control groups under dominant and recessive models.…”
Section: Ethodsmentioning
confidence: 99%
“…Several recent GWAS have shown that some non- HLA genes, such as STAT4 SNPs ( rs10168266 , rs11889341 , rs7574865 , rs8179673 , rs10181656 )[27], ESR2 rs1256030 T allele[28], CLEC16A, SOCS1, SPIB and SIAE genes[29], may also be significant risk factors for the progression of PBC. One study demonstrated that the downregulated expression of IL-12A in lymphoblastoid cell lines obtained from Han Chinese were markedly associated with the risk alleles of rs4679868 and rs6441286 ( P  =  0.0031 and 0.0073, respectively)[30]. Furthermore, the risk alleles of the 2 SNPs were observably related to a decreased expression of SCHIP1 gene that is 91.5 kb, located upstream of IL-12A and associated with susceptibility to celiac disease[30].…”
Section: Risk Factorsmentioning
confidence: 99%
“…One study demonstrated that the downregulated expression of IL-12A in lymphoblastoid cell lines obtained from Han Chinese were markedly associated with the risk alleles of rs4679868 and rs6441286 ( P  =  0.0031 and 0.0073, respectively)[30]. Furthermore, the risk alleles of the 2 SNPs were observably related to a decreased expression of SCHIP1 gene that is 91.5 kb, located upstream of IL-12A and associated with susceptibility to celiac disease[30]. These data have disclosed the IL-12/JAK-STAT signaling pathway as a pivotal etiologic factor for PBC.…”
Section: Risk Factorsmentioning
confidence: 99%